A caregiver perspective of complementary and alternative medicine use among patients with schizophrenia and bipolar disorders. Issue 4 (2nd October 2018) - Debrah, Akosua Bema; Buabeng, Kwame Ohene; Donnir, Gordon; Akwo Kretchy, Irene
Abstract: The World Health Organization estimates that about 40%–60% of patients with mental illness use Complementary and Alternative Medicine (CAM), but little is known about the types and outcomes of these CAM therapies in Ghana. This study therefore sought to describe the patterns of use and perceived outcome of CAM therapy among patients with schizophrenia and bipolar disorders in a health facility in Ghana. The qualitative study involved both clinical and family caregivers of patients with schizophrenia and bipolar disorders. Semi-structured interviews were conducted over a period of 3 months to identify the pattern of CAM use and perceived outcome from caregiver perspectives. The interviews were audio recorded, transcribed and analyzed thematically using NVivo 10. About 92% of family caregivers reported that their patients had used some form of CAM therapy. The therapies used included spiritual interventions (100%) herbal therapies (83%), dietary supplements (50%) and music therapies (6%). Both clinical and family caregivers perceived CAM therapies to be ineffective in resolving mental illness when used as an alternative to antipsychotic therapy. However when used as complementary, better outcomes were perceived. Spiritual interventions, herbal therapies, dietary supplements and music therapies were the types of CAM therapies used. Both negative and positive outcomes of CAM therapies were highlighted by caregivers. CAM use may therefore not be an alternative choice but rather complementary to mental health care.